التلقي العربي الراهن لسوسير في ضوء مخطوطاته المكتشفة (El-Wahat Journal for Research and Studies, 2017)
This Research Attempts To Capture The Features Of Arab Reception Of The Writings Of Ferdinand De Saussure, After The Discovery Of New Manuscripts Acquired In Saussure Orange Orchard In 1996. In Particular, These Manuscripts Contained Ideas That Conflicted With Some Of The Book "Lectures In Public Linguistics" Published By Paley And His Colleague, Which Roman Jacobson, In His Lectures At The Collège De France, Found It As A Lied Book.               Simon Bocky And Rudolf Engler Published 100 Pages Of These Manuscripts Under The Title "Writings In Public Linguistics" In 2002 In Paris, Representing One-Third Of These Manuscripts, Which Translated Into Thirteen Languages, None Of Them Are Arabic.               Are The Arabs Still Prisoners Of Ideas, Which Were Mentioned In The First Book, Which Became Axiomatic? Or Are There Researchers That Accompanied That Cognitive Development In The Field Of Linguistics? Have We Stopped At The Mere Transfer Of Knowledge And Represent It Or Is There An Arab Role In The Criticism Of Linguistic Knowledge? Keywords -  Susser - Arabic Receive - Orbital Manuscripts - Bali And Sishai - Writings In General Linguistics.